2003
DOI: 10.4049/jimmunol.171.1.477
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Changes in HIV-Specific Effector Activity in HIV-Infected Patients Starting Highly Active Antiretroviral Therapy in Primary Infection

Abstract: Both the magnitude and breadth of HIV-specific immunity were evaluated longitudinally on samples collected from six subjects starting highly active antiretroviral therapy (HAART) preseroconversion (group 1), 11 recently infected subjects starting HAART postseroconversion (group 2), five subjects starting HAART in the second half of the first year of infection (group 3), and six persons starting treatment in the chronic phase of infection (group 4). HIV-specific immunity was measured by IFN-γ ELISPOT, detecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 47 publications
1
30
0
2
Order By: Relevance
“…A similar situation may also occur during HIV infection. When viremia is controlled with effective antiretroviral therapy, or when antigen stimulation declines because of epitope mutation, the number of circulating HIV-specific CD8 T cells can substantially decline in chronically infected individuals (37)(38)(39)(40). One prediction of our study is that if antigen exposure is terminated during the early stages of infection (the acute phase), T cells may experience the necessary rest from antigen stimulation to differentiate into long-lived antigen-independent memory T cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar situation may also occur during HIV infection. When viremia is controlled with effective antiretroviral therapy, or when antigen stimulation declines because of epitope mutation, the number of circulating HIV-specific CD8 T cells can substantially decline in chronically infected individuals (37)(38)(39)(40). One prediction of our study is that if antigen exposure is terminated during the early stages of infection (the acute phase), T cells may experience the necessary rest from antigen stimulation to differentiate into long-lived antigen-independent memory T cells.…”
Section: Discussionmentioning
confidence: 96%
“…have shown that if antiretroviral therapy is initiated during the early phase of infection, HIV-specific CD8 T cells are more efficiently maintained (38,39). Also, it has been reported that during latent gammaherpesvirus infection of mice virus-specific CD8 T cells appear to be maintained in an IL-15-independent manner (41).…”
Section: Discussionmentioning
confidence: 99%
“…ϩ T cell response to HIV components is highly variable and generally found in long-term nonprogressor patients (19) or in individuals treated soon after infection (41). The HIV-specific CD4…”
Section: Discussionmentioning
confidence: 99%
“…During chronic infection, changes within the T-cell compartment include a significant skewing of the hierarchy of the immune response (1,38), improper maturation of effector Tcell populations (10), and changes in both the phenotypic and the functional quality of the HIV-specific CTL (7). Subjected to the protracted exposure to high doses of antigen, HIVspecific T cells have evolved elaborate homeostatic mechanisms that allow them to resist elimination while, simultaneously, they attempt to dampen immunopathogenesis (36).…”
mentioning
confidence: 99%